Charge Trapping in Mixed Organic Donor–Acceptor Semiconductor Thin Films. (22nd October 2014) - Nunomura, Shota; Che, Xiaozhou; Forrest, Stephen R.
<x xml:space="preserve">Abstract</x> A pump‐probe method, whereby trapped charges are optically induced to contribute to the total photocurrent, is applied to quantitatively determine the trap density in small‐molecule organic semiconductor thin films and donor–acceptor blends used in organic solar cells. The trapped charge density is correlated to the cell performance, and the dependence of charge trapping on the presence of nanocrystalline domains is discussed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>